The Study of Interior Monologue in Houshang Golshiri’s Shazdeh Ehtejab, Virginia Woolf’s Two Selected Novels, Mrs. Dalloway and to the Lighthouse; A Comparative Study - Narges Raoufzadeh; Fatemeh Sadat Basirizadeh; Shahrzad Mohammad Hosein (Budapest International Research and Critics University, 2020)
This paper aims to compare interior monologue which is a modern technique in three selected novels. Comparing Houshang Golshiri’s Shazdeh Ehtejab with Virginia Woolf’s Mrs. Dalloway and To the Lighthouse. Golshiri has made use of both direct and indirect interior monologues in his master piece, Shazdeh Ehtejab. An early example in Persian fiction which has a great emphasis on form and techniques of narrating the story. The present study will examine, in detail the creation of interior monologue through the minds of characters with reference to Golshiri’s Shazdeh Ehtejab and Virginia Woolf’s two selected novels, Mrs. Dalloway and To the Lighthouse. Focusing on the narrative techniques used by these two modernist writers and deals with illustrations from the novel and its explanations. The aim of this study is to show how Golshiri and Woolf try to move deeply into the character’s consciousness. They use the narrative technique, Interior Monologue, in their novels that deals with the flow of ideas, thoughts, feelings, and sensation.